تعزيز دور المصارف الإسلامية في تمويل المشروعات الصغيرة والمتوسطة في ليبيا في ضوء بعض التجارب الدولية (دراسة تطبيقية على المصارف الإسلامية في المنطقة الوسطى) - هرون عمران شعبان الهادي; عمر عبد الباسط سالم (Sharwes Scientific Journal, 2024)
This study aimed to identify and explain the role of Islamic banks in financing small and medium enterprises in Libya in light of some international experiences, and to achieve the goal of the the study, then prepare questionnaires and distribute them to a number of employees of Islamic banks working in Libya, as their number reached (80) questionnaires, and the method was used. Descriptive and analytical, and the study data were analyzed using the statistical program (SPSS20), where the data were tested using the arithmetic mean scale and the (T) test, and based on the results of the analysis, the study concluded: The necessity of financing small and medium enterprises in Libya in order to support and develop the workforce and provide job opportunities, which It contributes to lowering the unemployment rate, increasing the growth rate, developing local production, achieving economic diversification, and increasing sources of national income.